TEACHER’S STRATEGY TO BUILD CONNECTION WITH STUDENTS IN REDUCING THEIR ANXIETY IN LEARNING ENGLISH AT SMAN 1 JENEPONTO - Irawan, Arya Putra; Noni, Nurdin; Korompot, Chairil Anwar (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study aimed to find out (1) how effective is using strategy of building connections between teacher and students in reducing students’ anxiety in learning English, and (2) what are the factors that influence students’ anxiety in learning English. This study used a qualitative descriptive method and data was collected through observation and interview. The observation process was carried out in one meeting in class X.3 SMAN 1 Jeneponto and the interview process was conducted with eight students. The findings of this study can provide valuable insights to teachers, schools, and educational institutions in developing more effective teaching strategies in EFL learning contexts. The recommendations drawn from this study emphasize the need for ongoing teacher professional development to enhance relationship-building skills and implement supportive practices, ultimately fostering positive learning experiences for students.Keywords-- Strategy, Build Connection, Anxiety